PENGARUH SOSIALISASI PAJAK, KESADARAN PAJAK, DAN SANKSI PAJAK TERHADAP KEPATUHAN WAJIB PAJAK ORANG PRIBADI PPH FINAL PP 23 TAHUN 2018 - Umi Lailtul Izza; Moh. Amin; Arista Fauzi Kartika Sari (Universitas Islam Malang, 2020)
ABSTRACTThe purpose of this study is to know the effect of tax socialization, tax awareness, and tax penalty on individual taxpayer compliance PPh final PP 23 2018. Dependent variable in this study is the compliance of individual taxpayers final PPh PP 23 2018. Independent variables are tax socialization, tax awareness, and tax penalty. This research is a quantitative research. Data used in this study are primer data obtained from questionnaire at KPP Pratama Malang Utara. Data analysis technique used in this study uses multiple linear regression analysis. The results of the analysis show that partially the tax socialization has a significant positive effect on individual taxpayer compliance of PPh final PP 23 2018, tax awareness has a significant positive effect on individual taxpayer compliance of PPh final PP 23 2018, tax penalty have a significant negative effect on individual taxpayer compliance of PPh final PP 23 2018.Keyword: Tax socialization, Tax awareness, and Tax penalty on individual taxpayer compliance PPh final PP 23 2018.